Public perception on foreign migrants in Seremban / Siti Nordayana Mohd Yusof and Nuramirah Dzulkarnaen - Mohd Yusof, Siti Nordayana; Dzulkarnaen, Nuramirah (2022)
Foreign migrants are usually referred to as a threat to the country. People believe that immigration has had a detrimental impact on the country, and they are concerned that the number of immigrants is growing. Due to this issue, this study aims to investigate public perception on foreign migrants in Seremban. This study was carried out by using quantitative data. An online survey of 250 respondents from the public in Seremban from different gender, age, type of education as well as level of employment has participated in this study. Further, the questionnaires were distributed to obtain public opinion regarding the existence of foreign migrants in terms of religion, culture and legal system. Thus, in this study the researchers tend to analyse and discuss the findings on the relationship between the determinative of national identity which include culture, religion, and legal system and public perception of foreign migrants in Seremban. This demonstrates the three national identities can influence public perception and outcome of this research revealed culture is the main determinative that influences the public perception on foreign migrants in Seremban.